Housebroken at the Thought of Thinking Emancipa ted. Notes on the Transformation of Intellectual Work in Latin America (Andamios, Revista de Investigación Social, 2013)
Assuming the scene in which, during the last half century, most societies in the region have experienced profound political, economic and cultural changes, this article offers a critical reflection on the meaning and development of one of the social activities which have modeled this process in the region: the intellectual work. This discussion begins with a brief disambiguation of the category, defining its specificity. Then, we analyze diachronically some of the milestones in the fight to destabilize / stabilize a certain hegemonic view on it.   Finally, we offer some clues to assess the present and possibilities of this process in the region
Keywords: Epistemology; politics; intellectual work; hegemony; social change